2018
DOI: 10.1039/c8ra07654e
|View full text |Cite
|
Sign up to set email alerts
|

The penetration of a charged peptide across a membrane under an external electric field: a coarse-grained molecular dynamics simulation

Abstract: The processes of single polyarginine (R8) peptide penetration through planar and vesicle membranes under an external electric field are simulated via a coarse-grained molecular dynamics (CGMD) simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…Regardless of these differences, no simulation studies have observed the direct permeation of polyarginines, and the free energy barrier extracted for direct R 10 penetration across the 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) bilayer was estimated from biased simulations to be a massive ∼130 kJ/mol . Other simulation studies have suggested that a potential applied across the membrane could facilitate permeation, , yet it is not directly evident how a mechanism based on a potential gradient would discriminate between polyarginines and polylysines. Still, the membrane potential seems to play a role in cells, as demonstrated by a recent experimental study highlighting the role of ion channels in generating permeable pores .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of these differences, no simulation studies have observed the direct permeation of polyarginines, and the free energy barrier extracted for direct R 10 penetration across the 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) bilayer was estimated from biased simulations to be a massive ∼130 kJ/mol . Other simulation studies have suggested that a potential applied across the membrane could facilitate permeation, , yet it is not directly evident how a mechanism based on a potential gradient would discriminate between polyarginines and polylysines. Still, the membrane potential seems to play a role in cells, as demonstrated by a recent experimental study highlighting the role of ion channels in generating permeable pores .…”
Section: Introductionmentioning
confidence: 99%
“…Second, the external electric field was applied in all the simulations, including the WE simulations, and this electric field could contribute to the significant distortions of the membrane because our membrane has asymmetric distributions of DOPG lipids in both layers. It has been shown that the penetration of R8 within coarse-grained simulations depends on the external electric field 46 , and the authors showed that a higher electric field resulted in a short penetration time. The free energy calculations were also dependent on the electrostatic properties of the membrane 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The application of an electric field to the system of capzip capsule-bacterial membrane accelerates the bilayer disruption process, as reported previously. 112 This is due to perturbations caused to the membraneous arrangement by the inserting peptide through charged and hydrogen bond interactions mentioned before. These promote charged arginine residue insertion and initiate water penetration in the hydrophobic core of the membrane.…”
Section: Capzip In Solutionmentioning
confidence: 98%